2022
DOI: 10.3233/jrs-210051
|View full text |Cite
|
Sign up to set email alerts
|

Never events in orthopaedics: A nationwide data analysis and guidance on preventative measures

Abstract: BACKGROUND: Never Events (NE) are serious clinical incidents that are wholly preventable if appropriate institutional safeguards are in place and followed. They are often used as a surrogate of the quality of healthcare delivered by an institution. Most NEs are surgical and orthopaedic surgery is one of the most involved specialties. OBJECTIVE: The aim of this study was to identify common NE themes associated with orthopaedics within the National Health Service (NHS) of England. METHOD: We conducted an observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Precautionary principals have been made available including the WHO ‘Safe Surgery Checklist’ that aim to facilitate safe operative practices and prevent wrong site surgery and retained foreign bodies. However, a number of studies have demonstrated that NEs continue to occur 4,8,9 . Practices such as utilising radiopaque markers to indicate surgical side, for example, an ECG lead sticker, rather than relying on pen markings that are frequently covered by sterile drapes, may reduce the incidence of wrong site surgery 6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have demonstrated that NEs continue to occur. 4 , 8 , 9 Practices such as utilising radiopaque markers to indicate surgical side, for example, an ECG lead sticker, rather than relying on pen markings that are frequently covered by sterile drapes, may reduce the incidence of wrong site surgery. 6 Coloured markers on the distal portion of ureteric stents could be introduced to indicate ‘left’ and ‘right’ to help prevent removal stents from the wrong side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations